2011
DOI: 10.1002/jso.22138
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of the miR‐17‐92 cluster and its paralogs in colon cancer

Abstract: The miR-17-92 cluster and its paralogs were significantly elevated in patients with colon cancer, and heightened expression of miR-17 was associated with poor survival. Moreover, miR-17 and TNM staging were both identified as significant, but independent, prognostic biomarkers in colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 31 publications
4
61
0
Order By: Relevance
“…The miR17-92 cluster has been designated oncomir-1 (31), and can promote proliferation and angiogenesis, inhibit differentiation, and sustain cell survival (29,30). Elevated miR17-92 levels have been associated with invasion and metastasis of colorectal cancer cells (32), and poorer survival (33). miR19a and miR19b in particular are key oncogenic determinants (29,30), and both were significantly elevated with the HRM diet compared with the entry diet.…”
Section: Discussionmentioning
confidence: 99%
“…The miR17-92 cluster has been designated oncomir-1 (31), and can promote proliferation and angiogenesis, inhibit differentiation, and sustain cell survival (29,30). Elevated miR17-92 levels have been associated with invasion and metastasis of colorectal cancer cells (32), and poorer survival (33). miR19a and miR19b in particular are key oncogenic determinants (29,30), and both were significantly elevated with the HRM diet compared with the entry diet.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of miRs are crucial for tumorigenesis (11). miRs exhibit potential as diagnostic and prognostic biomarkers for colon cancer (12). Using miR expression patterns and target prediction, previous studies have observed that miR-185 expression is upregulated and results in loss of function of tumor suppressors in clear cell renal cell carcinoma (13) and lung squamous cell carcinoma (14).…”
Section: Discussionmentioning
confidence: 99%
“…42,43 The miR-17-92 cluster is frequently over-expressed in a variety of tumors like B-cell lymphomas, breast, colon, lung, pancreas, prostate, and stomach cancers. 44,45 Some other tumorigenic miRNAs induced by Myc are miR-19a/b, implicated in cancer metabolism and cancer cell survival, 46 miR-18a which contributes to angiogenesis 47 and miR-9 which modulates the expression of mediators of metastasis. 48 Myc can also actively repress the transcription of numerous miRNAs, including some members of the let-7 and miR-29 families, as well as miR-15a/16-1, miR-26a and miR-34a.…”
Section: Mirnas As Cancer Modulatorsmentioning
confidence: 99%